Loyalitas pelanggan dalam E-commerce: Menguji anteseden melalui Structural Equation Modeling: E-commerce's customer loyalty: Antecedents testing through Structural Equation Model - Soeharso, Silverius Y.; Putri, Angel Aulia; Lintang, Brigita Elizabeth; Chotimah, Devina Nur; Ningtyas, Lisa Dwi; Sundari, Resy (Faculty of Psychology Universitas 17 Agustus 1945 Surabaya, 2022)
Abstract This research is to determine the role of customer satisfaction as a mediator between utilitarian service quality and pleasant service quality on customer loyalty. The research used a questionnaire conducted online using the Google Form feature. Using a convenience sampling technique, 455 e-commerce users throughout Indonesia who are in the millennial to baby boomer generation (20-74 years) are found as research samples. The researcher developed a questionnaire using a Likert scale that modified the instruments from previous research to suit current research needs. The construct validity was reviewed again using CFA (confirmatory factor analysis). CFA results reveal that all indicators of the research measuring tool get a loading factor ≥ 0.50, construct reliability ≥ 0.70, and Average Variance Extracted ≥ 0.50. The data analysis process was carried out using Structural Equation Modeling. The study results show that customer satisfaction is a mediator between utilitarian and pleasant service quality on customer loyalty. This research implies that e-commerce can consider factors such as Customer Relationship Management, Customer Satisfaction, Pleasant Service Quality, and Utilitarian Service Quality to achieve customer satisfaction, ultimately maximizing company profits. Keywords: Customer Loyalty; Customer Relationship Management; Customer Satisfaction; Service Quality Pleasant; Service Quality Utilitarian Abstrak Penelitian ini untuk mengetahui peran customer satisfaction sebagai mediator antara service quality utilitarian dan service quality pleasant terhadap customer loyalty. Penelitian menggunakan kuesioner yang dilakukan secara online menggunakan fitur dari Google Form. Dengan teknik convenience sampling, didapatkan 455 pengguna e-commerce di seluruh Indonesia yang berada pada generasi millennials hingga generasi baby boomer’s (20-74 tahun) sebagai sampel penelitian. Peneliti mengembangkan kuesioner dengan menggunakan skala Likert yang memodifikasi instrumen-instrumen dari penelitian terdahulu agar sesuai dengan kebutuhan penelitian saat ini yang dilihat Kembali validitas konstruknya menggunakan CFA (confirmatory factor analysis). Hasil CFA mengungkapkan bahwa semua indikator alat ukur penelitian mendapatkan loading factor ≥ 0,50, construct reliability ≥ 0,70, dan Average Variance Extracted ≥ 0,50. Proses analisis data dilakukan dengan menggunakan Structural Equation Modeling. Hasil penelitian menunjukan bahwa customer satisfaction berperan sebagai mediator antara service quality utilitarian dan service quality pleasant terhadap customer loyalty. Implikasi dari penelitian ini, e-commerce dapat mempertimbangkan faktor-faktor seperti Customer Relationship Management, Customer Satisfaction, Service Quality Pleasant, dan Service Quality Utilitarian untuk mencapai kepuasan pelanggan yang pada akhirnya memaksimalkan keuntungan perusahaan. Kata kunci: Kepuasan Pelanggan; Kualitas Layanan Kesenangan; Kualitas Layanan Utilitarian; Loyalitas Pelanggan; Pengelolaan Hubungan Pelanggan